2022
DOI: 10.1101/2022.06.20.496763
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structural basis of LRPPRC-SLIRP-dependent translation by the mitoribosome

Abstract: In mammalian mitochondria, mRNAs are co-transcriptionally stabilized by LRPPRC. Here we show that LRPPRC forms a stable complex with SLIRP and mitoribosome to act as a carrier of genetic information, thus linking the gene expression system. The structure of translating human mitoribosome in complex with LRPPRC-SLIRP and mRNA shows how the mRNA is delivered for translation along a corridor formed by LRPPRC with proteins of the mitoribosomal small subunit mS31-mS39.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 88 publications
(176 reference statements)
0
10
0
Order By: Relevance
“…As a last test of our model, we analyzed how it performed when predicting mitochondrial protein synthesis in cells lacking LRPPRC, which associates with the ribosome and whose loss leads to disrupted polyadenylation and destabilized mt-mRNA 15,22,23 . We analyzed HEK293T cells lacking LRPPRC (LRPPRC KO ) and found that our quantitative HeLa-based model that performed well for other cell lines displayed little predictive power (Fig 6C).…”
Section: A Minimal Model Of Gene Expression Predicts Nuclear-and Mito...mentioning
confidence: 99%
See 2 more Smart Citations
“…As a last test of our model, we analyzed how it performed when predicting mitochondrial protein synthesis in cells lacking LRPPRC, which associates with the ribosome and whose loss leads to disrupted polyadenylation and destabilized mt-mRNA 15,22,23 . We analyzed HEK293T cells lacking LRPPRC (LRPPRC KO ) and found that our quantitative HeLa-based model that performed well for other cell lines displayed little predictive power (Fig 6C).…”
Section: A Minimal Model Of Gene Expression Predicts Nuclear-and Mito...mentioning
confidence: 99%
“…To test our approach in a system with different turnover rates, we analyzed LRPPRC knockout and matched control cells 5 . Mutations in LRPPRC cause the French-Canadian type of Leigh syndrome, and the LRPPRC protein is involved in mt-mRNA stabilization, poly(A) tailing, and translation (Fig S1O) 5,15,23,24 . Depletion of LRPPRC had profound effects on the steady-state levels of most heavy-strand encoded RNAs, as seen previously (Fig S1P).…”
Section: Differential Mt-mrna Degradation Rates Determine the Heavy-s...mentioning
confidence: 99%
See 1 more Smart Citation
“…So perhaps mTRANs evolved in land plants to compensate for increasing variability in mitochondrial ribosome binding site position, or conversely, the appearance of mTRANs allowed this variability to occur. These findings indicate that translational initiation by mitochondrial ribosomes occurs in a different way in plants as compared with in fungi and animals ( 12 , 61 ).…”
Section: Discussionmentioning
confidence: 94%
“…The human mitoribosome has a distinct structure, it receives mRNAs with involvement of Leucine-rich PPR-motif-containing protein (LRPPRC) and synthesizes 13 respiratory chain proteins delivered to the inner mitochondrial membrane via the OXA1L insertase ( Itoh et al, 2021 ; Singh et al, 2022 ). Cryo-EM has been instrumental in the structure determination of the mitoribosome, however, the description is currently limited to mitoribosomal proteins, rRNA, and associated factors, whereas important metabolic cofactors of potential therapeutic interest are largely excluded ( Aibara et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%